Membangun Kesadaran dan Peran Kader Pendamping Keluarga dalam Pencegahan Kekerasan Rumah Tangga di Desa Tejoasri, Lamongan - Suharnanik Suharnanik; Umar Sholahudin (LPMP Imperium, 2025)
Domestic violence (KDRT) is a social issue that requires serious attention, especially at the community level. This community service activity was carried out in Tejoasri Village, Lamongan on July 13, 2024. This research aims to build awareness and strengthen the role of family support cadres in efforts to prevent domestic violence in Village. The method used is a participatory approach involving PKK cadres as the main subject in empowerment activities. This program includes outreach about the types of domestic violence, its impact on families, as well as prevention strategies through education and mediation. The results of the service showed that after the training, there was an increase in cadres' understanding of domestic violence and their role as agents of change in their respective environments. Cadres are able to identify signs of domestic violence, provide education to vulnerable families, and build networks with related parties such as village officials and social service institutions. This program proves that empowering family support cadres can be a strategic step to create a community that is more caring and responsive to the issue of domestic violence.